Online Marketing Strategies of Thrifting Entrepreneurs in Sungai Penuh City from a Sharia Perspective: Strategi Pemasaran Online Pelaku Usaha Thrifting Di Kota Sungai Penuh dalam Persepektif Syariah - Putri, Veni Rahayu; Sarmigi, Elex; Nilda, Elvi (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the online marketing strategies implemented by thrift business operators in Sungai Penuh City using the 7P marketing mix approach, which includes product, price, place, promotion, people, process, and physical evidence. A descriptive qualitative method was employed, with data collected through interviews, observation, and documentation involving active online thrift sellers. The findings reveal that business owners actively utilize social media platforms such as Instagram, Facebook, and Shopee as their primary marketing tools. Product strategies focus on the quality and uniqueness of items, pricing is set competitively to attract young consumers, and promotions are carried out through visual content, giveaways, and live shopping features. Distribution processes are conducted online, supported by responsive customer service and attractive packaging to enhance the shopping experience. The study also finds that most of the marketing strategies applied reflect Islamic business ethics, including honesty (shiddiq), transparency (tabligh), and fairness (al-‘adl) in transactions. Therefore, the implementation of the 7P strategy aligned with sharia values has proven effective in enhancing competitiveness and expanding the market reach of thrift businesses in the region.